Pengaruh Ketimpangan Gender pada Perempuan terhadap Kondisi Ketersediaan Air Bersih Rumah Tangga di Desa Maradesa Timur Kabupaten Sumba Tengah - Okky Hetsmon U. P. Daytana; Johny A. R. Salmun (Media Kesehatan Masyarakat, 2021)
Clean water is a basic human need that supports the sustainability of life and public health. The ability to access clean water determines the amount of household clean water stored, domestic activities and clean, healthy behavior. Women are mostly responsible for water availability in East Nusa Tenggara (73,4%) and based on a gender perspective, this is gender inequality. The study aims to determine the influence of gender inequality on women on water availability in a household setting. This research was an analytical survey with a cross-sectional design. This research was conducted in East Maradesa Village, Central Sumba Regency in 2020 on 124 families with a sample of 95 women. The data analysis used multiple regression with α=0,05 (5%). The result indicated that gender inequality simultaneously had a significant effect on water availability with a meaning level of 9% (p=0.009; F=4.087; adjusted R2=0.09). The government needs to create a program with gender mainstreaming principles, and provide gender education through the family planning development program for communities in the village of East Maradesa, Central of Sumba.